2019
DOI: 10.1101/738054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute and Chronic Molecular Signatures and Associated Symptoms of Blast Exposure in Military Breachers

Abstract: Injuries from exposure to explosions rose dramatically during the Iraq and Afghanistan wars, which motivated investigations of blast-related neurotrauma and operational breaching. In this study, military "breachers" were exposed to controlled, low-level blast during a 10-day explosive breaching course. Using an omics approach, we assessed epigenetic, transcriptional, and inflammatory profile changes in blood from operational breaching trainees, with varying levels of lifetime blast exposure, along with daily s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…We previously reported that DNA methylation changes do not track with acute exposure to blast (21), and our present findings further support this in that DNA methylation appears to not be altered acutely pre-vs. post-blast exposure. As noted, for this experiment we used biospecimens from one site, FLWB, and examined DNA methylation changes in day-2 of training, pre vs. post blast exposure (approximately within 2 h post blast exposure, see Figure 1A for training protocol).…”
Section: Dna Methylation Changes Are Not Significantly Associated Witsupporting
confidence: 90%
See 3 more Smart Citations
“…We previously reported that DNA methylation changes do not track with acute exposure to blast (21), and our present findings further support this in that DNA methylation appears to not be altered acutely pre-vs. post-blast exposure. As noted, for this experiment we used biospecimens from one site, FLWB, and examined DNA methylation changes in day-2 of training, pre vs. post blast exposure (approximately within 2 h post blast exposure, see Figure 1A for training protocol).…”
Section: Dna Methylation Changes Are Not Significantly Associated Witsupporting
confidence: 90%
“…In the present study of military breachers, we set out to replicate previous findings, investigating effects of acute and chronic blast exposure on DNA methylation and reported symptoms at baseline across two military training sites-representing the largest DNA methylation study of breachers to date. In previous work, we found no significant DNA methylation changes associated with acute blast exposure (3-days post blast) (21). In the present study, we investigated whether blast induced DNA methylation changes could be detected at a more proximal time point, within 2-h post-blast exposure.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The blast wave propagation inside combat helmets is a complex problem, with the pressure focusing under the helmet dependent on several factors: 1) the shape of the helmet; 2) orientation relative to the source of the blast wave, and 3) the suspension system (i.e., number of pads, their distribution under the helmet and material properties). The mounting evidence suggests an association between occupational low-level blast exposure and acute adverse neurological effects [26], and related serum biomarkers changes [27,28]. The role of the helmet in the development of these effects is unclear at this time.…”
Section: Introductionmentioning
confidence: 99%